Kajian Hukum Peranan Forum P3SRS National dan KumHam dalam Upaya Penyelesaian Kisruh Apartemen yang Tidak Berkesudahan - Triana, Triana; Yasarman, Yasarman (PT Elaborium Elevasi Indonesia, 2025)
The highest legal regulation guidelines in apartment investment are in law of the Republic of Indonesia Number 20, 2011 Concerning Apartments. Where it is stated that what is purchased by an apartment investor is not only 1 small unit of his house to live in. But it is also an obligation to buy jointly owned land where the apartment stands, building/areas of share owned. Facilities such as corridors, parking, prayer rooms, swimming pool, and also buying jointly owned object. Such as elevators, installation cables, generators and so on which are jointly owned objects. Legally for all such joint ownership, it is mandatory to form a legal entity association to receive the transfer of jointly owned assets whose members are the owners and residents of the apartment. The facts found in the authors’s research over the past 10 years, 99% of the transfer have not been carried out. So that there is a high-level game that is allowed where, the building assets that are still collaterized by the developer in banking, in the end, whether intentionally or not, there is bankruptcy, where the apartment assets that have been sold to the public with a notarial deed, will be considered invalid. And this happens even in the courts throughout Indonesia as if turning a blind eye to the value of the Notarial AJB being considered invalid by itself. All land assets under the name of the developer will be confiscated by the curator. On another occasion, developer companies that go public also use apartment assets or building and condotels above them are recorded as company assets that are used to increase the selling value of share. Then become asssets that are assessed to issue long-term debt bonds. What about OJK and the ministry of Finance and the Ministry of PUPR as supervisors? They also automatically turn a blind eye as if they do not know that the apartment is subject to joint ownership law. On the other hand, the lower level as implementing and supervising government officials, are flocking to commit collective violations. There is a power struggle between developer employees and owners in terms of management, where investors, the owners who occupy, are charged monthly IPL bills which are said to be for maintaining the area and common property. As well as markups on financial values related to businesses held in apartments for the running of residential life. In our research, we fount that lower-level government officials who were given too much authority had overlapping powers. Starting from being an implementing officer, concurrently supervising, and concurrently acting as a supervisor, in the end the authority was easily bought by developers, especially when an error occurs, then the individual will be more intensive in trying to cover up the error by issuing regulations, and approvals as if everything was in accordance with the rules even though it clearly conflicts with the higher laws of the Republic of Indonesia.